Estimation of chlorophyll degradation into phaeophytin in Anaptychia ciliaris as a method to detect air pollution - Manrique, Esteban; Redondo, Fernando L.; Seriñá, Estela; Izco, Jesús (Lazaroa, 1989)
The influence of the following factors on the ratio of the phaeophytination index (OD 435 nm/OD 415 nm), in Anaptychia ciliaris (L.) Kóber is studied: the age ofthe lichen ihallus, the final concentration of the pigments, the transplantation to different areas on similar or distinct substrates and the pH value of the original or adopted substrate. The use of A. cilliaris as a bioindicator of acidic pollution is discussed.